CO2 footprint reduction and efficiency increase using the dynamic rate in overhead power lines connected to wind farms. (5th February 2018) - Arroyo, A.; Castro, P.; Manana, M.; Domingo, R.; Laso, A.
Highlights: Method to obtain an economic and environmental scenario for wind energy integration. Use of dynamic line rating operation to increase energy evacuated from wind farms. Dynamic line rating operation decreases the CO2 footprint and increases income. In 2015 dynamic line rating has saved more than 1100 tonnes of CO2 and 240, 000€. Latest 2014 CIGRE Standard using the most accurate unsteady thermal balance is used. Abstract: Since the first wind farms began operating in the early 1980s, several important factors have changed in the overall picture of energy politics worldwide. The total renewable wind energy capacity of Spain currently accounts for more than 20% of the total installed capacity, which makes integration into the grid challenging for wind farm owners as well as electricity transportation and distribution companies. The smart-grid concept, which focuses on real-time monitoring and dynamic rating operation of power lines, is an important component in the solution to these new challenges. This paper explains how a more efficient operation of energy-generating activities via dynamic rating of the electric grid due to a better knowledge of the main parameters contributes to more clean, renewable energy and decreases the CO 2 footprint. The dynamic rating operation of a Spanish overhead power line is analysed, and different scenarios are studied. The dynamic rate achieved in 2015 has saved more than 1100 tonnes of CO 2 and has generated over 240, 000 € of extra income. This dynamic rating operation also increased the actual annual energy generated from 231.5 GW h to 834.7 GW h with only a 2% greater loss along the line due to Joule and magnetic effects.